Ittihadoel Oelama: Integrasi Sosial Keagamaan di Palembang, 1939-1942 - Ramadoni, M. Desta; Ghofur, Alfian (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
The entry of various Islamic modern movements in Palembang in the early second decade of the 20th century brought changes, especially in the socio-religious aspect. Islamic modernists who carried a mission of change were rejected by traditionalist clerics who were rooted in differences in religious views. The dualism of the modernists and traditionalists continued into the early 1930s. Attempts at reconciliation by Islamic education leaders in Palembang emerged as a result of concern over the condition of Muslim relations that had not improved. This idea was realized with the establishment of the Islamic Religious Consideration Council (MPII) institution, although this institution eventually found a dead end after surviving nearly a decade. Then a positive response emerged from Islamic education leaders in Palembang by forming the Ittihadoel Oelama institution which has a vision and mission similar to the MPII institution. Several religious problems were successfully resolved both in the downtown area and in the rural areas. Ittihadoel Oelama quickly spread to various areas in Palembang. This study focuses on explaining the socio-religious integration efforts of Islamic education leaders in Palembang from 1939 to 1942. This research is divided into four stages, gathering sources, critiquing sources, interpreting and historiography or writing history. The research results cover two things, namely, first, the background to the emergence of social integration that started in the city center and second, the emergence of various Islamic educational institutions in Palembang became a supporting factor for the rapid process of social integration.